PENGARUH E-SERVICE QUALITY DAN PRICE TERHADAP CUSTOMER SATISFACTION DALAM MEMBENTUK REPURCHASE INTENTION - Wil Gania Nopenita (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine 1) the effect of e-service quality on customer satisfaction 2) the effect of price on customer satisfaction 3) the effect of e-service quality on repurchase intention 4) the effect of price on repurchase intention and 5) the effect of customer satisfaction on repurchase intention. The sample of this research is 200 respondents who are J.Co consumers who have purchased through a delivery website in the Greater Jakarta area. This research uses purposive sampling technique. The SEM method used in this study uses SPSS software version 25 and AMOS version 26. The results show that e-service quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, e-service quality has no positive and significant effect on repurchase intention, price has a positive and significant impact on customer satisfaction. significant effect on repurchase intention, and customer satisfaction has a positive and significant effect on repurchase intention.